Spatiotemporal evolution and driving factors of soil erosion function in a typical basin of the alpine region in the upper Yellow River - Xiaomei Kou; Qi Li; Zhen Song; Zhen Song; Qin Yu; Qin Yu; Baicheng Niu; Baicheng Niu; Baicheng Niu; Shan Wang; Shan Wang; Kaifang Mu; et al. (Frontiers in Plant Science)
In recent years, soil erosion has become increasingly severe in the Tibet Plateau, especially in the upper Yellow River Basin. Although numerous studies have been conducted on soil erosion in this region, most of them are limited to short time spans and fail to reflect the temporal variations of soil erosion at long-term scales. In this study, the spatiotemporal changes in soil erosion intensity and soil conservation function were evaluated using the InVEST model, and driving factors were identified using Geodetector in the Shagou River watershed from 1980 to 2020. The results showed that over the past 40 years, the Shagou River watershed mainly suffered mild erosion, the soil erosion intensity increased by 81.40% from 1980 to 2000, reaching a peak of approximately 1292.49 t/(km²·a). From 2000 to 2020, it decreased by 40.45% with 769.63 t/km²·a, indicating a clear improvement trend. From 1980 to 1990, the growth rate of soil conservation function was most significant, reaching 25.89%, while the growth rate from 2010 to 2020 was relatively small, only 6.23%. Over the past 40 years, the total soil conservation function increased by 1.12×10⁷ t, with a growth rate of 88.24%, reflecting the effectiveness of soil conservation measures. In addition altitudes, slopes, and land use types had significantly affected both on actual soil erosion intensity and soil conservation function. Geodetector analysis revealed that the primary factors influencing soil erosion intensity were vegetation cover and elevation, along with their two - factor interaction. Regarding the soil conservation function, the main influencing factors were elevation and precipitation, with the interaction dominated by elevation. This study should provide a theoretical basis and scientific reference for ecological protection and sustainable development in the alpine region of the upper Yellow River Basin.